Decreased Expression of CDC25A in Azoospermia as the Etiology of Spermatogenesis Failure - DA Suryandari; YH Midoen; L Yunaini; S Setyaningsih; HJ Freisleben (JRI, 2018)
Background: Spermatogenesis is a tightly regulated developmental process of male germ cells. The stages in spermatogenesis are mitosis, meiosis and spermiogenesis. One of the genes playing a role in meiosis is Cell Division Cycle 25A (CDC25A). Decreased expression of CDC25A is associated with failure of spermatogenesis and sperm retrieval. Infertility examination for azoospermia has been limited on histological examination. Hence, molecular research to find marker genes for infertility will improve the examination of testis biopsies. Methods: This research is a cross sectional study of 50 testicular biopsies with Johnsen scoring categories from scoring 2 to 8. Analysis of mRNA expression used qPCR and protein expression using immunohistochemistry. Statistical analysis with Spearman correlation was considered significant at p<0.05. Results: The result showed that transcript level and protein expression of CDC25A decreased in score 5 of Johnsen scoring categories. Moderate Spearman rho correlation (r=0.546) between mRNA relative expression and protein expression of CDC25A was significant at p<0.01. Conclusion: Decreased expression of CDC25A is associated with meiotic arrest as the etiology of spermatogenic failure in many azoospermic men.